The relationship between helminth infections and low haemoglobin levels in Ethiopian children with blood type A. Issue 3 (19th May 2016) - Degarege, A.; Yimam, Y.; Madhivanan, P.; Erko, B.
Abstract: The current study was conducted to evaluate the nature of association of ABO blood type with helminth infection and related reduction in haemoglobin concentration. Stool samples were collected from 403 school-age children attending Tikur Wuha Elementary School from February to April 2011. Helminth infection was examined using formol-ether concentration and thick Kato–Katz (two slides per stool specimen) techniques. Haemoglobin level was determined using a HemoCue machine and ABO blood type was determined using the antisera haemagglutination test. Nutritional status was assessed using height and weight measurements. Out of 403 children examined, 169, 120, 96 and 18 had blood type O, A, B and AB, respectively. The prevalences of helminth infections were 46.9% for hookworm, 24.6% for Schistosoma mansoni, 4.2% for Ascaris lumbricoides, 1.7% for Trichuris trichiura and 58.3% for any helminth species. The relative odds of infection with at least one helminth species was significantly higher among children with blood type A (adjusted odds ratio (AOR), 2.10; 95% confidence interval (CI), 1.28–3.45) or blood type B (AOR, 2.08; 95% CI, 1.22–3.56) as compared to children with blood type O. Among children infected with helminths, mean haemoglobin concentration was lower in those with blood type A than those with blood type O (β, −0.36; 95% CI, −0.72 to −0.01). The relative odds of hookworm infection (AOR, 1.78; 95% CI, 1.08–2.92) and related reduction in haemogobin levels (β, −0.45; 95% CI, −0.84 to −0.04) was higher among children with blood type A as compared to those with blood type O. Although the difference was not significant, the relative odds of S. mansoni or A. lumbricoides infections and related reduction in haemoglobin levels was also higher in children with blood type A or B as compared to children with blood type O. In conclusion, children with blood type A are associated with an increased risk of helminth, particularly hookworm, infection and related reduction in haemoglobin level. The mechanisms by which blood type A makes children susceptible to helminth infection and a related reduction in haemoglobin level ought to be investigated.